Alpha-Ketoglutarate, an Endogenous Metabolite, Extends Lifespan and Compresses Morbidity in Aging Mice - Asadi Shahmirzadi, Azar; Edgar, Daniel; Liao, Chen-Yu; Hsu, Yueh-Mei; Lucanic, Mark; Asadi Shahmirzadi, Arash; Wiley, Christopher D; Gan, Garbo; Kim, Dong Eun; Kasler, Herbert G; Kuehnemann, Chisaka; Kaplowitz, Brian; et al. (Cell metabolism, 2020)
Metabolism and aging are tightly connected. Alpha-ketoglutarate is a key metabolite in the tricarboxylic acid (TCA) cycle, and its levels change upon fasting, exercise, and aging. Here, we investigate the effect of alpha-ketoglutarate (delivered in the form of a calcium salt, CaAKG) on healthspan and lifespan in C57BL/6 mice. To probe the relationship between healthspan and lifespan extension in mammals, we performed a series of longitudinal, clinically relevant measurements. We find that CaAKG promotes a longer, healthier life associated with a decrease in levels of systemic inflammatory cytokines. We propose that induction of IL-10 by dietary AKG suppresses chronic inflammation, leading to health benefits. By simultaneously reducing frailty and enhancing longevity, AKG, at least in the murine model, results in a compression of morbidity.